Assessing the Fear of Package Theft - Hicks, Melody (American journal of criminal justice, 2022)
A rapidly growing crime problem in the United States and abroad, package theft is a phenomenon that is of persistent and significant concern to the public. However, the academic study on the subject has been neglected. Because package theft is understudied, the impact it has is difficult to understand, and the crime itself is hard to address. This present study defines package theft, informs readers about package theft, and examines online retail consumers’ fear of the crime. Fear of crime research has typically focused on the fear of violent crime, or it has concentrated on an abstract fear of crime. This study broadens the literature about fear of crime by examining fear of a specific crime, package theft, using an index of eleven questions measuring behavioral, cognitive, and affective impacts. Survey data of 562 participants from 49 states reveal that nearly one quarter (23.8%) have experienced package theft. Fear of package theft was statistically significant among the variables gender (women more than men), residential location (urban and suburban more than rural), and previous victimization of package theft. Additionally, the fear of package theft directly or vicariously harmed consumers and resulted in risk mitigation and risk avoidance behaviors. The present study demonstrates the usefulness of measuring fear through an index of multiple variables, for a specific crime, within an environmental context.